Determination of the Resistance of Hot Mix Asphalt Samples Prepared Under Different Conditions Against Wheel Tracking - Alataş, Taner; Yilmaz, Mehmet; Kök, Baha Vural (Fırat University, 2018)
The present study aimed to examine the resistance of pure hot mixes and those prepared with 4% of three different polymers two types of SBS (styrene-butadiene-styrene) and one type of EVA (ethylene-vinyl-acetate) against permanent deformation. Samples were prepared with application of vibration so that they would have 4% void ratio using a roller compactor and without this application. The effect of vibration application during sample preparation on the wheel track formation was also assessed in the current study. Wheel track tests demonstrated that use of additives increased the resistance of hot mixes against wheel track formation. It was also determined that the most effective additive was EVA. Furthermore, it was determined that application of vibration during sample preparation increased the resistance of specimens against permanent deformation.
Keywords: Engineering; Mühendislik